Women's representation in the media - Lont, Cindy; First Light Video Publishing ([s.l.] : GMU-TV; Venice, CA. : First Light Video Publishing (distributor), 2005)
This program focuses on four areas, which is the reclaimed history of women who created media, the media portroyal of women, women's inclusion in the media work-force and how we read, see and hear from the media. This program is a perfect introduction to women, minorities and media courses or a section on a media in women's studies.
Title from title screen.
Editor, Steve Watson.
DVD format.
Keywords: Women in mass media; Mass media and women; Women -- Employment